Evidence-based research project In support of the President's 8-point agenda
This collection of Policy Briefs is based on the research studies carried out under the “Evidence-based Research in Support of the President’s 8-Point Agenda” project, with funding from the House of Representatives, and implemented by the Ateneo Center for Economic Research and Development of Ateneo de Manila University.